Pengaruh Perceived Usefulness & Kepercayaan terhadap Intensitas Penggunaan Teknologi E-Wallet sebagai Alat Transaksi - Muhammad Aulia Utama; Diah Priharsari; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
E-wallet is an electronic service that allows to store data on payment instruments such as credit cards and electronic money, which can also be used to make payments. Consumers' attention or interest in using e-wallet will grow along with perceived usefulness and trust in service providers and the technology used by e-wallet providers. In acceptance of technology and adoption of e-wallet the importance of perceived usefulness has been proven, which implies that a higher level of technology usefulness is in the intention to use by merchants or merchants and is well received by consumers. This research is a quantitative research using SEM-CB. After distributing the questionnaires to 327 respondents, the results of the data processing showed that 4 hypotheses were accepted with Hypothesis 1 and Hypothesis 3 being accepted at a P-Value value of 0.000, then hypothesis 2 with a P-Value value of 0.005, and hypothesis 4 being accepted with a P-Value value of 0.003. Based on the results of the research that has been done, it can provide a new perspective along with references to the usefulness of e-wallet technology as a transaction tool.